북한의 상징공간과 기억의 정치 - 정영철; Youngchul Chung (한국과 국제정치, 2024)
2023년 『로동신문』에는 김정은이 현철해의 묘비 앞에 무릎을 꿇고 헌화하는 상징적인 사진이 게재되었다. 김정은이 무릎을 꿇었던 공간은 애국열사릉으로서 북한의 최고 성지라고 할 수 있다. ‘수령’ 김정은 마저도 무릎을 꿇어야 하는 공간으로서 열사릉은 북한 체제의 정당성을 응축하고 있는 곳이다. 한편, 김정은 시대의 정치를 상징과 기억의 측면에서 더듬어 본다면, 현실의 정치 및 경제적 과제와 긴밀하게 연결된다. 기억이 집단적이고 사회적인 것이라면, 북한이 현재 보여주고 있는 상징조작 및 동원과 그에 기초한 기억의 정치의 이면에는 바로 현실의 문제를 풀어가기 위한 역사적 기억의 생산과 재생산에 있다고 할 수 있다. 그런 점에서 김정은의 ‘기억의 정치’는 1970년대의 시대 정신의 호명, 전승 세대의 호명에 뒤이어 상징공간으로 ‘열사릉’의 재조명으로 이어지고 있다. 앞으로도 김정은의 상징과 기억의 정치는 지속될 것으로 예상된다. 간부 혁신과 인민들의 사상적 무장을 통해 경제적 실리와 실적을 평가하고, 그를 위한 상징과 기억을 끊임없이 재소환할 것이다. 또한, 북한은 현 시대를 신냉전으로 규정하면서 미국 및 남한과의 대결을 우선시하고 남북관계를 ‘교전중인 적대적 국가’로 규정하였다. 그렇다면, 이러한 객관적 환경을 반영하여, 또 다른 상징과 기억을 동원하는 새로운 상징정치가 나타날 것으로 예상된다. 그리고 그 방향은 지금보다 더욱 더 ‘국가’로서의 기억과 상징을 호명하고 동원하는 것으로 나타날 것이다. In 2023, the Rodong Sinmun published an iconic photo of Kim Jong-un kneeling in front of Hyon Chol-hae’s tombstone and paying his respects. The space where Kim Jong-un knelt is Yeolsa-Reung (the Mausoleum of the Patriots), North Korea’s holiest shrine. As a space where even the suryong(The Great Leader) Kim Jong-un must kneel, the tomb encapsulates the legitimacy of the North Korean regime. On the other hand, the politics of Kim Jongun’s era is closely linked to the real political and economic challenges of the country in terms of symbols and memory. If memory is collective and social, then behind North Korea’s current manipulation and mobilization of symbols and the politics of memory based on them is the production and reproduction of historical memory to solve real-life problems. In that sense, Kim Jong-un’s ‘politics of memory’ is leading to the reemergence of the Yeolsa-Reung as a symbolic space, following the call of the zeitgeist of the 1970s and the call of the generations that preceded him. Kim Jong-un’s politics of symbols and memory is expected to continue. It will evaluate its economic performance through cadre innovation and ideological arming of the people, and will constantly recall symbols and memories. In addition, North Korea has defined the current era as a new Cold War, prioritizing confrontation with the United States and South Korea and defining the two Koreas as ‘belligerent hostile states.’ Reflecting this objective environment, a new symbolic politics that mobilizes different symbols and memories is expected to emerge. And the direction will be to invoke and mobilize the memory and symbols of the ‘state’ even more than now.